Hölder continuity of weak solutions to subelliptic equations with rough coefficients - Sawyer, E. T. (Eric T.), 1951- (Memoirs of the American Mathematical Society, 2006)
Introduction Comparisons of conditions Proof of the general subellipticity theorem Reduction of the proofs of the rough diagonal extensions of Hormander's theorem Homogeneous spaces and subrepresentation inequalities Appendix Bibliography.